Indigenous Knowledge on The Uses of Medicinal Plants by Dayak Benuaq Society, West Kutai, East Kalimantan - Siti Susiarti (The Ethnobiological Society of Indonesia, 2005)
Indonesia is well known as one of the biodiversity centers in the world, including natural drugs that highly needed recently. Indigenous knowledge on medicinal plants, especially in Dayak Benuaq society in West Kutai, East Kalimantan is presented. Sixty species of plants, belonging to 55 genera and 31 families, have been used as medicinal plants by Dayak Benuaq society. Most of them are grown widely. Some of medicinal plants can be used to cure approximately 38 kinds of diseases. Traditional ceremony, known as balian, is also used during medication.